2009
DOI: 10.1007/s10703-009-0073-1
|View full text |Cite
|
Sign up to set email alerts
|

Weakly-relational shapes for numeric abstractions: improved algorithms and proofs of correctness

Abstract: Weakly-relational numeric constraints provide a compromise between complexity and expressivity that is adequate for several applications in the field of formal analysis and verification of software and hardware systems. We address the problems to be solved for the construction of full-fledged, efficient and provably correct abstract domains based on such constraints. We first propose to work with semantic abstract domains, whose elements are geometric shapes, instead of the (more concrete) syntactic abstract d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 40 publications
(97 reference statements)
0
48
0
1
Order By: Relevance
“…Intuitively, this means that all hyperplanes defined through inequalities actually touch the enclosed volume. However, the octagons may contain redundant inequalities, and therefore it will be interesting to see if simplification is worthwhile [2] and, if so, whether nonredundant octagons can be directly derived using SAT.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Intuitively, this means that all hyperplanes defined through inequalities actually touch the enclosed volume. However, the octagons may contain redundant inequalities, and therefore it will be interesting to see if simplification is worthwhile [2] and, if so, whether nonredundant octagons can be directly derived using SAT.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…5.3.4), we have a representation-aware widening. A more semantic widening, that is independent from the DBM chosen to represent the zone arguments, has been proposed by Bagnara et al [2009], based on an alternate normal form that tries to remove as many constraints as possible (i.e., put bounds to +∞).…”
Section: Indeed At Each Iteration Either X or Y Is Set To [−∞ +∞] mentioning
confidence: 99%
“…The efficiency of these domains has then been improved, firstly through algorithmic improvements, by Bagnara et al [2008a] and Bagnara et al [2009] and, secondly, through implementation improvements, such as leveraging the parallel execution available in GPU by Banterle and Giacobazzi [2007]. Alternate weakly relational domains, also based on transitive closure algorithms, include the less expressive pentagon domain by Logozzo and Fähndrich [2010] and the more expressive "Two variables per inequality" domain by .…”
Section: Bibliographic Notesmentioning
confidence: 99%
“…The Octagon domain [18] is a widely deployed [6] abstract domain, whose popularity stems from the polynomial complexity of its domain operations [2,9,18] and ease of implementation [13]. Systems of octagon constraints are conventionally represented [18] using difference bound matrices (DBMs).…”
Section: Introductionmentioning
confidence: 99%
“…Running Callgrind [25] on an off-the-shelf abstract interpreter (EVA [8]), equipped with the de-facto implementation of Octagons (Apron [13]) on AES-128 code (taes of table 1) revealed that 36% of all the function calls emanated from qmpq init which merely allocates memory and initialises the state of a rational number. When working over rationals, these indirect costs dampen or mask algorithmic improvements obtained by refactoring [2] and reformulating [9] domain operations.…”
Section: Introductionmentioning
confidence: 99%